Clinical hints to diagnosis of attenuated forms of Mucopolysaccharidoses - Miriam Rigoldi; Elena Verrecchia; Raffaele Manna; Maria Teresa Mascia (BMC, 2018)
Abstract The mucopolysaccharidoses (MPS) are clinically similar but also heterogeneous in terms of major or minor involvement of different organs/systems, burden of disease, and rate of progression. The attenuated forms of MPS, due to their less severe presentations, are more difficult to diagnose and often receive a significantly delayed diagnosis. On the other hand, the diagnosis is very important since the attenuated forms may benefit from earlier treatments. The aim of this paper is to describe the natural history and the clinical signs useful to arise a suspicion of an attenuated form of MPS. MPS patients usually show a cluster of signs and symptoms, one of which may be the trigger for an evaluation by a specialist. Individuals with attenuated MPS are mostly cognitively normal, and dysmorphisms of the facies may be mild or absent. The most frequently involved organs/systems are the osteoarticular system, heart, and eyes. These patients may also have hepatosplenomegaly, hearing loss, and respiratory problems. When they are referred to a specialist (rheumatologist, cardiologist, ophthalmologist, surgeon, orthopedist, etc.) for their main complaint, the other signs and symptoms are likely to be missed in the medical history. To avoid missing data and to save time, we propose a semistructured medical history form to be filled in by the patients or their caregivers while waiting for evaluation by a specialist.